Codeswitching from Indonesian to English Encountered in the Three Naila Farhana's YouTube Videos - Auliza, Nur; Sudarsono; Suhartono, Luwandi; Susilawati, Endang; Ikhsanudin (Kirana Publisher (KNPub), 2023)
This study aims at describing the types and functions of codeswitching encountered in Naila Fahana’s YouTube videos. The data were collected from Naila Farhana YouTube channel with three selected videos entitled Mau Tips Lancar Belajar Bahasa Inggris, Pelajari 5 Kunci Sukses (Be Fluent in English, learn 5 successful keys), Cara Bahasa Inggris Tanpa Ngeblank (Learn English without Going Blank), American Accent_ Cara Belajar Aksen Amerika (American Accent_ How to Learn American Accent). This research was a descriptive study in which the writer described types of codeswitching using a theory of Peter Stockwell and functions of codeswitching using a theory of Marasigan. In collecting the data, this study utilized human instrument in which the researcher as the main source. Then, the data were sorted out of the corpora from video transcriptions with 4,622 words in total. The findings of this study showed that the dominant type of codeswithing is intrasentential switching (IaSCS) with 102 data out of 123 data and the dominant function of codeswitching is message of qualification (MQ) with 50 data out of 123 data. This research covered three types and seven functions of codeswitching as a discussion for further linguistic study on codeswitching.